ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP KEPUTUSAN PINDAH KELAS PERAWATAN PASIEN BPJS - Aldianur Khairani; Dewi Anggraini; Dwidjo Susilo (RAGAM: Journal of Statistics & Its Application, 2023)
This study aims to analyze the effect of patient satisfaction with hospital services on the decision to move BPJS patient care classes at Ulin Hospital, Banjarmasin. The data collection technique used is quantitative, namely distributing questionnaires to BPJS patients. Participants in this study amounted to 75 people. Data analysis used ordinal logistic regression analysis. The level of patient satisfaction is measured using 4 factors, namely Tangible, Reliability, Assurance, and Empathy. The results showed that the patient satisfaction factors that had a significant effect were Assurance and Empathy. Overall, these two variables influenced the satisfaction assessment of patients treated at Ulin Hospital, Banjarmasin, by 27.5%.